Effect of progressive muscle relaxation on nurses’ work-related stress: A quasi-experimental study - Indra Frana Jaya KK; Iman Apriyadi (Science Center Group, 2026)
Background: Nurses experience substantial work-related stress due to high workload, organizational demands, and emotional labor in hospital settings. Persistent occupational stress may contribute to burnout, reduced job performance, and compromised quality of care. Progressive Muscle Relaxation (PMR) has been recognized as a non-pharmacological technique to reduce psychological stress; however, empirical evidence focusing on hospital nurses remains limited. Objective: This study aimed to examine the effect of Progressive Muscle Relaxation on nurses’ work-related stress in a public hospital setting. Methods: A quasi-experimental study with a one-group pretest–posttest design was conducted among 35 nurses at RSUD Siti Fatimah, South Sumatra Province. Total sampling was applied to recruit eligible participants. Work-related stress was measured using the Expanded Nursing Stress Scale (ENSS), consisting of 57 Likert-scale items. The intervention consisted of Progressive Muscle Relaxation administered once daily for seven consecutive days. Data were analyzed using descriptive statistics and paired sample t-test to compare pre- and post-intervention stress scores. Results: The majority of participants were female (74.3%) and professional nurses (57.1%), with more than three years of work experience (57.1%). The mean stress score decreased from 125 before the intervention to 87.5 after the intervention. The mean difference in stress scores was 35.5 (SD = 13.06), and the paired t-test revealed a statistically significant reduction in stress levels (p = 0.001). Conclusion: Progressive Muscle Relaxation significantly reduced nurses’ work-related stress after seven consecutive sessions. The findings suggest that PMR is a feasible and practical intervention for stress management in hospital settings. Integration of structured relaxation programs into occupational health strategies may enhance nurses’ psychological well-being and support safer clinical practice